GCF CARICOM AgReady Project Consultation - Gregoire Carai, Nekelia (Inter-American Institute for Cooperation on Agriculture (IICA), 2023)
Guest speakers: Mrs. Nekelia Gregoire Carai, Technical Specialist, Inter-American Institute for Cooperation on Agriculture (IICA) - Dominica, Mrs. Kelly Witkowski, Technical Specialist, Inter-American Institute for Cooperation on Agriculture (IICA) - Costa Rica, Dr. Lyndelle St. Ville, Stakeholder Consultant, DataShore - St. Lucia, Dr. Arlette St. Ville, Stakeholder Consultant, DataShore - St. Lucia, Ms. Candice Ramessar, Gender Consultant, Freelance Consultant - Guyana, Ms. Dianne Dormer, Climate Smart Agriculture Specialist, Freelance Consultant - Jamaica